New opportunities of multiple criteria methods - Podvezko, Valentinas; Podviezko, Askoldas (Lietuvos matematikos rinkinys, 2013)
A substantial amount of practical problems are solved by using multiple criteria optimisation methods, e.g. evaluation and comparison of social and economic development of counties of a country,  choice of the optimal technology project, comparison of investment or innovation projects, ratings of universities, choice of the best strategy, and many similar tasks. The solution of the problem is to determine the best alternative from several available ones, or ranking of alternatives in accordance with the chosen pursued objective. Nevertheless, often a set of alternatives to choose from is not available, and a single object must be evaluated. This could be a unique technology, innovation, or investment project, enterprise. The aim of this paper is to apply principles, ideas, and philosophy of multiple criteria methods, and to propose evaluation methods for evaluation of a single object.
Keywords: MCDM; relative evaluation; absolute evaluation; hypothetical reference objects